Characterization of physical and chemical attributes of a yellow latosol in the Municipality of Paragominas - PA (Research, Society and Development, 2021)
Soil aptitude is directly related to the environmental functions that are performed within a given ecosystem, be it natural or management. In view of the impacts generated through inadequate use of the soil, the main objective of this work was to perform the physical-chemical characterization of a yellow latosol located in the municipality of Paragominas, in the southeastern region of the state of Pará, in the northern region of Brazil. Samples of the soil were collected at two depths: 0 - 20 cm and 20 cm - 40 cm, respectively. And from that, laboratory analyzes were performed, such as natural humidity, color (Munsell's method), pH measurement, particle size and organic carbon content. The method used in this research was quantitative and qualitative. The results showed that the color of the sample indicated a predominance of red (R), acidic pH. In terms of granulometry, it was classified as clay-loam, which is also known as medium texture, and, finally, the organic carbon analyzed indicated variations, which are directly related to the difficulty of oxidizing the samples. In summary, it was possible to observe that the soils collected at the two depths indicated low dissimilarity between them, presenting slightly different results despite the change in the horizon.